2014
DOI: 10.1186/1472-6874-14-42
|View full text |Cite
|
Sign up to set email alerts
|

A survey on depression among infertile women in Ghana

Abstract: BackgroundThe desire of many young women to become parents may be influenced by the premium placed on children by society. In Africa, children are highly valued for social, cultural and economic reasons. Infertile and childless women in Africa are therefore confronted with a series of societal discrimination and stigmatization which may lead to psychological disorders such as anxiety and depression. Even though some research has been done on the prevalence of infertility in Ghana, very little is known about th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

13
101
8
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 95 publications
(129 citation statements)
references
References 24 publications
13
101
8
7
Order By: Relevance
“…Infertile and childless women in Africa are therefore confronted with a series of societal discrimination and stigmatization which may lead to emotional problems such as anxiety and depression. [22] The study reveals that 73% of the study infertile women were childless; this is consistent with Dyer et al [23] who stated that, the stigma of childlessness is so great that infertile women are socially isolated and neglected. Also, Alhassan et al [22] stated that infertile women are often excluded from social occasion and ceremonies or may even be deprived and perceived as inauspicious.…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…Infertile and childless women in Africa are therefore confronted with a series of societal discrimination and stigmatization which may lead to emotional problems such as anxiety and depression. [22] The study reveals that 73% of the study infertile women were childless; this is consistent with Dyer et al [23] who stated that, the stigma of childlessness is so great that infertile women are socially isolated and neglected. Also, Alhassan et al [22] stated that infertile women are often excluded from social occasion and ceremonies or may even be deprived and perceived as inauspicious.…”
Section: Discussionsupporting
confidence: 79%
“…[22] The study reveals that 73% of the study infertile women were childless; this is consistent with Dyer et al [23] who stated that, the stigma of childlessness is so great that infertile women are socially isolated and neglected. Also, Alhassan et al [22] stated that infertile women are often excluded from social occasion and ceremonies or may even be deprived and perceived as inauspicious. Available evidence suggests that the social and psychological complications of infertility are particularly profound for African women as compared to men as reported by Arthur et al [24] This is well observed in this study where 52% of the infertile group required medical advice within the first two years of their marriage; this reflects the importance of having children among Egyptian females.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations